Prevalence of Enteric Parasites and Related Environmental Factors in Two Native Communities of Zulia State - Adriana Maldonado; Zulbey Rivero Rodríguez; Glenis Chourio Lozano; Iris Díaz; Marinella Calchi La Corte; Ellen Acurero; Angela Bracho; Juan Bárcenas (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2008)
The objective of the investigation was to relate the prevalence of enteric parasites to environmental factors in two native communities of Zulia State. Fecal samples were analyzed using the copro-parasitology test and concentration technique, for 168 Japrería individuals located in the Perijá Mountain Range and 283 Añú in the Sinamaica Lagoon. Soil samples from the respective zones were evaluated, measuring pH, organic carbon, electric conductivity, extractable phosphorus, calcium, magnesium, interchangeable potassium and texture. Precipitation data were also analyzed. A high prevalence of enteric parasites was found in both communities (Japrería 83.93%, Añú 85.16%). Protozoa and polyparasitism dominated, observing Blastocystis hóminis in first place for both populations. Regarding helminths, Ancylostomídeos prevailed among the Japrería and Trichuris trichiura among the Añú. Soil at the Japrería locality was less sandy than that of the Añú and received greater annual average precipitation. Conclusions were that among the environmental factors evaluated, the soil is important because of its texture, vegetable cover and precipitation, influencing its capacity to retain humidity, an element that determines different distribution patterns in the prevalence of geohelminths.